The Effect of Management Control System and Financial Leverage on Start-up Performance: Business Financial Literacy as Moderation - Sihite, Henny Yunita; Aziza, Nurna (Dinasti Publisher, 2025)
This study aims to examine the effect of management control systems and financial leverage on the performance of start-ups fostered by the Bengkulu University Technology Business Incubator (IBT). The sample in this study consists of 37 start-ups engaged in various business sectors, including agriculture, food and beverages, technology, and handicrafts. This study also analyzes the role of business financial literacy as a moderating variable that is expected to strengthen or weaken the effect of management control systems and financial leverage on start-up performance. Data analysis was conducted in two stages. The first stage used multiple linear regression to test the direct effect between the independent variables on start-up performance. The second stage uses Moderated Regression Analysis (MRA) to test the interaction effect between independent variables and moderating variables on performance. The regression model was analyzed using SPSS version 26 software, with classical assumption testing including normality, multicollinearity, and heteroscedasticity tests to ensure model validity. The results showed that management control system and financial leverage have a positive and significant effect on start-up performance. In addition, business financial literacy proved to have a significant moderating role, with a tendency to weaken the relationship between management control system and performance, and strengthen the relationship between financial literacy and performance.